Keynesian Dominance in Crisis Therapy - Kristina Spantig (Graduiertenkolleg 'Konstitutionelle Grundlagen globalisierter Finanzmärkte - Stabilität und Wandel', 2013)
This paper scrutinizes the debate of Keynes and Hayek concerning the adequate re- sponse to economic crises from a historical perspective. In a first step the develop- ment of the Keynesian economic theory, its ascent during the Great Depression and its use during financially sound times is analyzed. In a second step the Hayekian cri- tique to discretionary government intervention and its long run consequences is scru- tinized. In the last step it is analyzed why, in the wake of a crisis, short-run oriented Keynesian therapy dominates long-run Hayekian therapy as in the most recent crisis.
urn:nbn:de:gbv:27-20131126-113025-3
Keywords: B20; E12; E52; E62; 330; Keynes; discretionary fiscal policy; monetary policy